Analysis Quality of Specialist Doctor Services and Patient Satisfaction at H.Abdul Manan Simatupang Hospital in Kisaran Regency - Amelia Dwifika Putri; Destanul Aulia; Zulfendri (Pena Cendekia Insani, 2021)
Introduction: Patient dissatisfaction with hospital services is inextricably linked to the low quality of services provided byspecialist doctors in hospitals that fall short of patient expectations.The quality of specialist services can be determined by theinformation and education provided by the specialist doctor, theemotional support provided by the specialist doctor, the accessibilityto the specialist doctor's services, and the physical comfort providedby the specialist doctor. Method: This research is an explanatorysurvey research with a quantitative approach that uses a crosssectional design. This study was conducted at Sultan Abdul MananSimatupang Hospital in Asahan Regency in January 2018-December2018. The population in this study were all patients who receivedinpatient services both class I, class II, class III and VIP at SultanAbdul Manan Simatupang Hospital and samples in this study asmany as 30 patients. Data analysis used chi-square test and crosstabulation. Result : The results of this study indicate that the majorityof patients are dissatisfied with the services provided by specialistdoctors. The quality of services that make patients dissatisfied isinformation and edukasi, emotional support while access to servicesand physical comfort is quite satisfying. There is a relationshipbetween information and education, emotional support provided byspecialist doctors with patient satisfaction. Conlusion : Specialistsdoctor in Sultan Abdul Manan Simatupang Hospital in AsahanRegency must provide optimal services, especially services inproviding information and education to patients.